2000
DOI: 10.1021/es990633h
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Effluents as a Source of Gadolinium in the Aquatic Environment

Abstract: Total annual Gd emission of a hospital offering a maximum spectrum medical services using Gd complexes in magnetic resonance imaging was computed and independently measured by ICP/MS. The Gd emission was between 2.1 and 4.2 kg per year, yielding a theoretical concentration of 8.5−30.1 μg per L in the hospital's effluent. Gd concentrations measured on different days were below detection limit (1 μg per L) and 55 μg per L, and annual average concentrations were between 10.5 and 20.5 μg per L as calculated from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
100
0
5

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(110 citation statements)
references
References 20 publications
5
100
0
5
Order By: Relevance
“…This is observed in populated and industrialized regions (Gd/Gd* >2 and up to 1500, closer to the source of contamination, Bau and Dulski, 1996;Nozaki et al, 2000;Elbaz-Poulichet et al, 2002). The source of the Gd is most likely gadopentetic acid, Gd(DTPA) 2-, which is used in magnetic resonance imaging (Kummerer and Helmers, 2000). A significant number of the Yamuna river water samples show positive Gd anomalies (shale-normalized Gd/Gd* values 0.95 to 1.32, Fig.…”
Section: Europium Cerium and Gadolinium Anomalies In River Watersmentioning
confidence: 81%
“…This is observed in populated and industrialized regions (Gd/Gd* >2 and up to 1500, closer to the source of contamination, Bau and Dulski, 1996;Nozaki et al, 2000;Elbaz-Poulichet et al, 2002). The source of the Gd is most likely gadopentetic acid, Gd(DTPA) 2-, which is used in magnetic resonance imaging (Kummerer and Helmers, 2000). A significant number of the Yamuna river water samples show positive Gd anomalies (shale-normalized Gd/Gd* values 0.95 to 1.32, Fig.…”
Section: Europium Cerium and Gadolinium Anomalies In River Watersmentioning
confidence: 81%
“…Gd 3þ toxicity appears to be associated with its action as a blocker of Ca 2þ channels because its ionic radius is nearly equal to that of divalent Ca 2þ (Sherry et al, 2009). Gd chelates are stable complexes and are not metabolized and so they enter the environment unchanged (Kümmerer and Helmers, 2000). It has been estimated that between 70 and 300 g Gd is released each day into the environment Abbreviations: hpf, hours post fertilization; Gd, gadolinium; PMCs, primary mesenchyme cells.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, quite a large part of cephalosporins gets access to the surface water by run-off. On the other hand, cephalosporins entering the municipal wastewater collection system could survive in the conventional wastewater treatment practices as well (Dodd et al, 2010;Gulkowska et al, 2008), and have been frequently found in the effluents from wastewater treatment plants (Le Corre et al, 2012;Kümmerer and Helmers, 2000;Kümmerer, 2001Kümmerer, , 2010Heberer, 2001;Sarmah et al, 2006;Leung et al, 2012;Lin et al, 2010). Furthermore, the cephalosporins are discharged with wastewater effluents to surface water which may serve as drinking water sources.…”
Section: Introductionmentioning
confidence: 99%